Lepicerus larva still unknown: a correction (Coleoptera: Lepiceridae, Phalacridae) - Lawrence, John F.; Ślipiński, Adam; Beutel, Rolf G.; Newton, Alfred F. (Zootaxa, 2019)
The larva of Lepicerus inaequalis Motschulsky was described by Lawrence et al. (2013) based on several early instars and one late instar collected among wet leaves and debris near Gamboa, Panama. The identification was based on collection of an adult Lepicerus in a similar habitat nearby and a combination of characters found in other myxophagan immatures but not known in other beetle larvae. We accepted this identification with some reservations, but a misinterpretation of one feature in the original description plus an unexpected new source of evidence makes it likely that our identification was incorrect. The one misinterpreted feature in this larva was the retraction of the ventral mouthparts. Reexamining the larvae, it was found that a pair of tendons extending mesally from the hypostomal rods were misinterpreted as maxillary bases. The mouthparts are definitely protracted, which is expected with long hypostomal rods. The new source of evidence is somewhat complicated, as explained below.